Differences in predicting athletic burnout and in moderating its relationship with life satisfaction in competitive and leisure athletes - Karolina Grebner; Alena Michel-Kröhler; Tabea Werner; Stefan Berti; Michèle Wessa (Scientific Reports, 2024)
Abstract The effects of athletic burnout on life satisfaction vary greatly between individuals, but few studies have examined influencing factors, such as coping mechanisms, that explain these differences. While athletes’ performance levels seem to influence the development of burnout symptoms, there is a lack of studies examining different performance levels separately. The present study therefore investigated the predictors of athletic burnout in competitive and leisure athletes separately, as well as possible moderators influencing the relationship between burnout and life satisfaction in these groups. A cross-sectional online study with sport-specific and general questionnaires was conducted. Latent (e.g., resilience) and manifest variables (e.g., stress) were included as predictors of athletic burnout in two structural equation models (competitive: robust RMSEA = 0.065, robust CFI = 0.946; leisure: robust RMSEA = 0.067, robust CFI = 0.937) with data from 422 athletes (M age = 23.65; range = 16–67; 43% female, 57% male). Additionally, moderation analyses with coping mechanisms as moderators between burnout and life satisfaction were conducted. Results show that predictors of athletic burnout differ between performance levels. Furthermore, there is a significant moderation effect (p < 0.01) for positive self-concept in competitive sports. Approaches for future research and the development of target group-specific interventions are discussed.